Collaborative Care in Primary Care: The Influence of Practice Interior Architecture on Informal Face-to-Face Communication—An Observational Study. (January 2021) - Morgan, Sonya; Pullon, Susan; McKinlay, Eileen; Garrett, Susan; Kennedy, Jonathan; Watson, Bruce
Background: Quality patient care in primary care settings, especially for patients with complex long-term health needs, is improved by interprofessional collaborative practice. Effective collaboration is achieved in large part by frequent informal face-to-face "on-the-fly" communication between team members. Research undertaken in hospitals shows that interior architecture influences informal communication and collaboration between staff. However, little is known about how the interior architecture of primary care practices might facilitate or hinder informal communication and collaboration among primary care staff. Objectives: This research explores the influence of primary care practice interior architecture on face-to-face on-the-fly communication for collaborative care. Methods: An observational study was undertaken to compare face-to-face informal interactions between staff in three primary care practices of differing interior architecture. Data collected from practices included: direct observations floor plans, photographs, interviews, and surveys. Results: Most primary care staff engaged in frequent, brief face-to-face interactions, which appeared to be key to the delivery of effective collaboration. Features of primary care practice designs that were associated with increased frequency of staff interaction included shared spaces, staff proximity/visibility, and the presence of convenient circulatory and transitional spaces where staff were able to easily engage in timely on-the-fly communication with colleagues. Conclusions: The interior architecture of primary care practices has an important impact on staff collaboration. Although more research is needed to investigate further details in more practices, close attention should nevertheless be paid to maximizing opportunities for brief face-to-face communication in well-designed shared spaces in primary care practices.